2012
DOI: 10.1590/s1984-29612012005000005
|View full text |Cite
|
Sign up to set email alerts
|

Canine visceral leishmaniasis: seroprevalence and risk factors in Cuiabá, Mato Grosso, Brazil

Abstract: In Brazil, canine visceral leishmaniasis (CVL) is endemic and the number of cases in humans and dogs has increased in the Midwest region. A transversal study was carried out in endemic areas from Cuiabá, State of Mato Grosso, to assess data on seroprevalence and risk factors associated to canine infection. Four hundred and thirty (430) dogs were randomly evaluated through indirect fluorescence antibody test (IFAT) considering variables related to the animals, the environment and the knowledge by owners on CVL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 31 publications
7
26
2
5
Order By: Relevance
“…Anti-Leishmania spp. antibodies in the states of Mato Grosso and Mato Grosso do Sul have been reported by other researchers, with frequencies higher than that observed in this work and according to the particular characteristics of each region under study (NUNES et al, 2001;CORTADA et al, 2004;ANDRADE et al, 2009;ALMEIDA et al, 2012;SOUSA et al, 2013;BRITO et al, 2014). This may be related to the opportunist feeding behavior of the vector.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Anti-Leishmania spp. antibodies in the states of Mato Grosso and Mato Grosso do Sul have been reported by other researchers, with frequencies higher than that observed in this work and according to the particular characteristics of each region under study (NUNES et al, 2001;CORTADA et al, 2004;ANDRADE et al, 2009;ALMEIDA et al, 2012;SOUSA et al, 2013;BRITO et al, 2014). This may be related to the opportunist feeding behavior of the vector.…”
Section: Discussioncontrasting
confidence: 48%
“…Furthermore, the presence of livestock and agriculture may represent a risk of disease because it can stimulate the establishment of sand flies in these environments, especially regarding that in the Pantanal area livestock activities and tourism related to fishing and safari are among the most important economic activities (MOREIRA JUNIOR et al, 2003;ALMEIDA et al, 2012). Based on these facts, the study of leishmaniasis in Brazil's Pantanal wetland is of great significance to human and animal health and it is possible to conclude that future research on this disease is essential in this region.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the frequency of healthy dogs and those presenting any clinical changes were similar; however, it is not possible to attribute such changes to infection by T. gondii, given the endemic nature of other diseases such as canine ehrlichiosis and canine visceral leishmaniasis (SILVA et al, 2010;ALMEIDA et al, 2012).…”
Section: Introductionmentioning
confidence: 75%
“…In a study in Cuiabá, MT, on 430 dogs from urban and rural locations, Almeida et al (2012) found that the mean prevalence of dogs seropositive for visceral leishmaniasis was 22,1%. In an endemic area of San Luis, state of Maranhão, Barbosa et al (2010) observed a high frequency of positive dogs (67%), and in the same state, Felipe et al (2011) found a canine infection rate of 47.8% in the municipality of Raposa.…”
Section: Discussionmentioning
confidence: 99%